STRATEGI PEDAGANG KAKI LIMA (PKL) DI JALAN NAGA SAKTI KOTA PEKANBARU - Donni Maston Simamora; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted on Naga Sakti Street, Simpang Baru Village, Bina Widya District, Pekanbaru City. The purpose of this study was to determine the profile of informal sectors (PKL) on Naga Sakti street, Pekanbaru city and to determine the strategy of informal sectors (PKL) on Naga Sakti street, Pekanbaru city. This study uses a descriptive qualitative research method, using purposive sampling of subjects that have determined the criteria in this study. Based on the specified criteria, five informants were found who were the research subjects. The results of this study are informal sectors (PKL) on Naga Sakti street, Pekanbaru city, who set up trade stalls permanently and do not move from trading locations and have trading permits, experienced a decrease in income from trading due to the very severe COVID-19 pandemic. Impact on the street vendors. Informal sectors (PKL) have three strategies for survival, namely an active strategy by utilizing or optimizing their potential, the potential of family members, increasing trading time and having side jobs to increase income. The two passive strategies are making savings by minimizing spending on family food needs such as eating before trading or bringing supplies from home when they want to trade, and managing family finances wisely, one of which is by not buying primary and secondary needs if they are not needed in the family and taking advantage of assistance. which exists. Third, the network strategy is to build relationships with fellow traders to complement each other's trading needs, build good relationships with families and relationships with business owners or official institutions such as banks, pawnshops by borrowing money for business capital and family needs. Keywords: Street Vendor Profiles, Informal Sectors (PKL), Survival Strategies